Understanding the costs and benefits of digital platforms and the implications for policymaking and regulation - Ramonette B. Serafica; Queen Cel A. Oren (Philippine Institute for Development Studies (PIDS), 2021)
This paper examines how digital platforms work and reviews their impacts across different sectors. We look at the experience of the Philippines and other countries focusing on e-commerce and ride-hailing/delivery service platforms. Government-initiated platforms and applications in agriculture were also discussed. The review of the literature highlights the various positive and negative effects of digital platforms in achieving inclusive and sustainable economic development. The emergence of various digital platforms and the technologies that drive them will continue to shape our economy and society in ways that we cannot yet fully anticipate. How well we manage the risks and exploit the opportunities will largely depend on finding the appropriate role of the government in the platform economy and the quality of regulatory governance.
Keywords: 330; digital platforms; platform economy; multisided platforms